Differences in nutritional status and level of physical activity among adolescents living in urban and rural areas of Montenegro - national study - Erol Vrevic; Pavle Malovic; Dragan Bacovic; Danilo Bojanic; Aldijana Nokic (BMC, 2024)
Abstract Background Nutritional status and physical activity are important factors for adolescent health. These factors may vary by the place of residence. This study aims to assess the nutritional status and physical activity levels, as well as their variations by the place of residence. Methods The sample consisted of 1503 adolescents (46.3% male; 53.7% female), with a mean age of 15.7 ± 0.7 years. Nutritional status was assessed using Body Mass Index (BMI), Waist-to-Height Ratio (WHtR), and Body Fat Percentage (BF). Physical activity levels were assessed using the PAQ-C questionnaire. Differences in nutritional status among adolescents living in urban and rural areas were analyzed using Chi-square test (p ≤ 0.05), while differences in physical activity levels were analyzed using an independent samples t-test (p ≤ 0.05). Results In terms of BMI, 14.7% of males were overweight and 10.1% were obese, while 12% of female adolescents were overweight and 3.1% were obese. There were no differences in nutritional status among adolescents living in urban and rural areas (BMI, WHtR, BF). Male adolescents in rural areas had significantly higher physical activity levels compared to urban areas (p = 0.032). They showed higher activity scores during a spare time (p = 0.002), physical education classes (p = 0.002), little breaks (p = 0.007), and lunchtime (p = 0.034). Female adolescents showed significance only in spare time activity (p = 0.020). Conclusion The differences in nutritional status among adolescents living in urban and rural areas were not found. However, male adolescents living in urban areas showed lower physical activity levels than their rural counterparts. Strategies should be implemented to promote physical activity among adolescents in urban areas, and attention should be given to the further urbanization process to create improved conditions for engaging in physical activity.